(3QSGdI aj Mce TQH GdbghI (B( (3GdHf (B)s
(3ChdgG (B:s
(3GdMeO ddg gPg UhQI hGbYI eMQQI s
(3BNQgG (B:s
(3cd gDdGA CFeI C(B'(3dGe EbJUQfG YdiCSeGFge Nha GdEWGdI hGdedd hGddg Gdehab Hefg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS YTQs
(3JVefJ BQGA LedI ef GdYdeGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs